2012
DOI: 10.1590/s0080-62342012000400031
|View full text |Cite
|
Sign up to set email alerts
|

Desconfortos físicos decorrentes dos tratamentos do câncer de mama influenciam a sexualidade da mulher mastectomizada?

Abstract: The objective of this integrative review is to analyze the scientific production addressing the sexuality of women with breast cancer following mastectomy, focused on the effects that the physical discomfort due to cancer treatments have on their sex life. The search included articles published in the period between 2000 and 2009 on the MEDLINE, LILACS and PsycINFO databases, using the following descriptors: mastectomy, breast neoplasms, sexuality, sexual behavior, amputation, psychosexual development, and mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
0
9
1
7
Order By: Relevance
“…A review study that identified the impact of physical discomforts derived from the treatment on the sexuality of a woman with breast cancer evidenced that changes in body image and selfimage affected their sexual experience and marital satisfaction (Cesnik & Santos, 2012). Corroborating, another study shows that breast preservation relates to the maintenance of a more positive body image, helping women maintain their psychological wellbeing, resume routine activities and preserve their QL (Moreira & Canavarro, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review study that identified the impact of physical discomforts derived from the treatment on the sexuality of a woman with breast cancer evidenced that changes in body image and selfimage affected their sexual experience and marital satisfaction (Cesnik & Santos, 2012). Corroborating, another study shows that breast preservation relates to the maintenance of a more positive body image, helping women maintain their psychological wellbeing, resume routine activities and preserve their QL (Moreira & Canavarro, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Resumption of social relationships, leisure activities, work and family life leads women to concerns related to their own existence, making them feel satisfied with the end of the treatment, but mentally and physically exhausted with prolonged exposure to therapeutic procedures (Cesnik & Santos, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It also highlighted a high susceptibility of women with breast cancer to physical and psychosocial stressors, contributing to a lowering in the quality of life of these women [20].…”
Section: Discussionmentioning
confidence: 99%
“…There are several treatments towards this disease, even though surgery is the most employed one (Sawada, Nicolussi, Okino, Cardozo, & Zago, 2009). Surgery may also cause significant changes in female self-image since the patients may have to live without the extirpated breast and the consequences of mutilation, with serious interference on their sexuality and conjugal satisfaction (Cesnik & Santos, 2012).…”
Section: Introductionmentioning
confidence: 99%